9 Understanding clusters of risk factors across different physical contexts for the prediction of injuries among canadian youth. (9th June 2015) - Russell, Kelly; Davison, Colleen; King, Nathan; Pike, Ian; Pickett, William
Abstract : Statement of purpose: Among Canadian youth, injury is the most common reason for Emergency Department presentations. Youth who participate in activities that increase their injury risk commonly engage in multiple risk-taking behaviours. This study aimed to determine if clusters of risk-taking behaviours were associated with injury in youth and how these patterns varied across contexts. Methods/approach: Risk-taking behaviours and injury outcome data were collected from grade 9–10 students using the 2009–2010 Health Behaviours in School-Aged Children Survey (n = 10, 429). Principal components analysis identified clusters of risk-taking behaviours. Within each identified cluster, the degree of risk-taking was stratified into quartiles from none to highest. Adjusted risk ratios with 95% confidence intervals described the association between injury risk and the degree of risk-taking behaviour within each cluster. For each cluster, the injury risk was stratified by home, school, neighbourhood, and sport contexts. Results: Four clusters of risk-taking behaviour were identified – substance use, high-risk substance use, externalising behaviours (eg, stealing, impaired driver/passenger), and physical activity. For each cluster, there was a significantly increased injury risk and the highest injury risk occurred among youth who performed the most risk-taking behaviours. Youth who engaged in the highest level of physical activity had the highest injury risk (aRR: 1.98; 95% CI: 1.75–2.23) compared with non-participants. Compared with youth who engage in no externalising behaviours, those who engaged in the highest level had the highest injury risk (aRR: 1.63; 95% CI: 1.48–1.79). The gradient between increased risk-taking behaviours and increased injury risk was most pronounced for injuries sustained in the neighbourhood. Conclusions: This study delineates clusters of risk-taking behaviours that put youth at progressively increasing injury risk. Significance and contributions: Understanding the clustered and cumulative nature of increasing risk-taking behaviours, and how these relate to context, highlight potential modifiable factors that may be important avenues for intervention.